A Comparison of Intimate Partner Violence Strangulation Between Same-Sex and Different-Sex Couples - Messing, Jill Theresa (Journal of interpersonal violence, 2021)
Strangulation is a common and dangerous form of intimate partner violence (IPV). Nonfatal strangulation is a risk factor for homicide; can lead to severe, long-term physical and mental health sequelae; and can be an effective strategy of coercion and control. To date, research has not examined strangulation within same-sex couples. The objective of this cross-sectional, observational research is to identify whether and to what extent the detection of strangulation and coercive control differs between same-sex and different-sex couples in police reports of IPV. Data (n = 2,207) were obtained from a single police department in the southwest United States (2011-2013). Bivariate analyses examined differences in victim and offender demographics, victim injury, violence, and coercive controlling behaviors between same-sex (male-male and female-female) and different-sex couples (female victim-male offender). Logistic regression was used to examine associations between strangulation, victim and offender demographics, coercive controlling behaviors, and couple configuration. Strangulation was reported significantly more often in different-sex (9.8%) than in female and male same-sex couple cases (5.2% and 5.3%, respectively; p < .05). Injury, however, was reported more frequently in same-sex than in different-sex couples (p < .05). Couple configuration (p < .05), coercive control (p < .05), and injury (p < .05) significantly predict strangulation. Findings suggest that nonfatal strangulation occurs within at least a minority of same-sex couples; it is possible that underdetection by law enforcement makes it appear less common than it actually is. Regardless of couple configuration, timely identification of strangulation and subsequent referral to medical and social service providers is essential for preventing repeated strangulation, life-threatening injury, and the long-term health effects of strangulation.